Usability evaluation For Arts, Culture, And Heritage Mobile Application Among Asnaf Entrepreneurs In Perlis - Usolludin, Hazi Hafizah; Saad, Mazni; Abdul Latif, Samshul Amry; Mohamad Ali, Afiza; Izzudin, Muna; Fairuz, Mona (Research and Innovation Unit Centre for Foundation Studies, International Islamic University Malaysia, 2023)
The usage of mobile applications for knowledge-sharing through digital literacy has increased in tandem with the growth in the adoption of digital technology. Similarly, in an attempt to minimize the negative effects of today’s globalization on local cultural heritage, mobile applications as a learning platform are widely used. However, in this context, poor application usability could be a factor in the adoption and usage of mobile applications among users. This includes ineffective features and poor design of mobile applications. This study aims to examine the adoption of an arts, cultural, and heritage mobile application developed and termed the Virtual Asnaf Business Center (ABC) among Asnaf entrepreneurs. A qualitative approach, particularly physical face-to-face interview sessions, was employed for this mobile application testing The results of the study found that although the majority of respondents are in business for more than a decade, only one respondent advertised their products on social media, suggesting that the respondents were generally not IT-savvy. Suggestions include digital adoption training, the inclusion of user manuals and tutorials, as well as additional features to the mobile application. The study’s findings are important for mobile application developers in designing userfriendly mobile applications focusing on arts, culture, and heritage in Malaysia.